HEAT TREATMENT OF ALUMINIUM MATRIX COMPOSITE (AMC) REINFORCEMENT ORGANOCLAY FOR AUTOMOTIVE APPLICATION - Yulius Eka Agung (Jurnal Vokasi Indonesia, 2017)
Aluminum Matrix Composites (AMC) reinforced montmorillonite (MMT) was performed using cationic surfactant , Artificial Aging and stir casting method. The content of MMT as a filler is 3%wt. Characterization were performed using Xray Difractometer, ultrasonic testing, SEM, and Hardness Vickers. The results show increase in crystallographic parameter, decrease in density, shiffting in XRD pattern and increase in hardness.Keywords: metal, composite, matrix, aluminum, AMC, MMC, organoclay, heat treatment MMT, artificial aging,stir casting, automotive